Optimizing the Role of Talent First Line Manager through Nursing Resource Development Strategy Based on External and Internal Analysis: Case Report - Friska Lestari; Choriati Nuormanisa; Ilham Cahyo Nugroho; Taufik Kurahman; Inyalebe Talaohu; Teuku Muhammad Zaini; Rr Tutik Sri Hariyati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Abstract The role of the first line man The role of the first line manager (FLM) is strategic in improving hospital service quality as a link between managerial policies and clinical practice. However, the transition from clinical nurse to managerial position, along with the complexity of healthcare services, creates challenges in managing nursing human resources. This case report aims to develop a strategic human resource development plan to support the transition of FLM talent at Hospital X Jakarta. The study participants consisted of 41 head nurses serving as First Line Managers (FLMs) at RS X. The method used is a descriptive-analytic approach with field study, using primary data (interviews and observations) and secondary data (literature and documents). The analysis applies SWOT, IFE-EFE matrices, IE matrix, and TOWS, integrated with the Balanced Scorecard (BSC). The results show that Hospital Strengths include educational qualifications, clinical experience, and a structured head nurse selection system. Weaknesses include uneven managerial competencies, a non–talent-based appointment system, and high workload. Opportunities arise from digitalization, accreditation demands, and HR development, while threats include burnout risk, hospital competition, and regulatory changes. ager (FLM) is strategic in improving hospital service quality as a link between managerial policies and clinical practice. However, the transition from clinical nurse to managerial position, along with the complexity of healthcare services, creates challenges in managing nursing human resources. This case report aims to develop a strategic human resource development plan to support the transition of FLM talent at Hospital X Jakarta. The method used is a descriptive-analytic approach with field study, using primary data (interviews and observations) and secondary data (literature and documents). The analysis applies SWOT, IFE-EFE matrices, IE matrix, and TOWS, integrated with the Balanced Scorecard (BSC). The results show that Hospital Strengths include educational qualifications, clinical experience, and a structured head nurse selection system. Weaknesses include uneven managerial competencies, a non–talent-based appointment system, and high workload. Opportunities arise from digitalization, accreditation demands, and HR development, while threats include burnout risk, hospital competition, and regulatory changes. The recommended strategies include strengthening leadership competencies through continuous training, developing mentoring systems, implementing objective talent management, and optimizing the FLM role in improving service quality and patient safety.